Factors affecting costs of groundwater development in Sub-Saharan Africa. [Abstract only]. - Xenarios, Stefanos; Pavelic, Paul (2011)
Greater use of groundwater in Sub-Saharan Africa is a pre-requisite for improved human welfare, and achievement of the Millennium Development Goals. However, the costs associated with groundwater development are poorly defined. Also, at the macro-scale, little attention is given to indicators which may influence groundwater development in Sub-Saharan Africa. This study initially identifies the costs of groundwater drilling in eleven Sub-Saharan African countries. A cross-country analysis between representative development indicators and the groundwater drilling costs is used to identify distinguishing features. The results indicate that mobilization and demobilization costs, together with pumping test costs most significantly affect the total costs of groundwater drilling. Further, demographic, land, water and health related parameters may influence groundwater development. Better attention to the individual cost factors and to the examined indicators could help to design more coherent groundwater policies in Sub-Saharan Africa.